1995
DOI: 10.1002/etc.5620140409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the synthetic pyrethroid insecticide, esfenvalerate, on larval leopard frogs (Rana spp.)

Abstract: Leopard frog (Rana spp.) tadpoles exposed to esfenvalerate in the laboratory experienced a decrease in activity at concentrations as low as 1.3 μg/L and exhibited a convulsive, twitching response at concentrations of 3.6 μg/L. The 96‐h median lethal concentration was 7.29 μg/L. Temperature influenced amphibian mortality; the mortality concentration‐response slope at 22°C was significantly greater than at 18°C. Tadpoles exposed in a pond showed the same responses (inactivity, convulsive actions, and death) at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Our results are in contrast to most studies that investigated the effect of temperature on pesticide toxicity for amphibian larvae in acute toxicity studies. In Materna et al [ 20 ] leopard frog larvae ( Lithobates sp. ; former R .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are in contrast to most studies that investigated the effect of temperature on pesticide toxicity for amphibian larvae in acute toxicity studies. In Materna et al [ 20 ] leopard frog larvae ( Lithobates sp. ; former R .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in contrast to most studies that investigated the effect of temperature on pesticide toxicity for amphibian larvae in acute toxicity studies. In Materna et al [20] leopard frog larvae (Lithobates sp. ; former R. pipiens complex) showed higher mortalities in 96-h acute toxicity tests for the pyrethroid insecticide esfenvalerate at 22˚C than at 18˚C.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on the combined effects of temperature and pesticides on amphibians reveal contrasting results. Some observed that higher temperatures increased toxicity [19][20][21], while others showed a reduced toxic effect of pesticides on exposed amphibians [22][23][24]. For Oligosoma polychroma, a skink (reptile) and thus also an ectothermic vertebrate species, even a heatseeking behavior was observed, that can be interpreted as response to increase the metabolism to better deal with stress after exposure to a glyphosate formulation [25].…”
Section: Leeb Et Almentioning
confidence: 99%